Supplementary damping controller design for SSSC to mitigate sub-synchronous resonance. (February 2016) - Panda, S.; Baliarsingh, A.K.; Mahapatra, S.; Swain, S.C.
Abstract: This paper proposes to use gravitational search algorithm (GSA) to design a supplementary sub-synchronous damping controller for the static synchronous series compensator (SSSC) device to damp the torsional oscillations. The IEEE second benchmark model (SBM) which is a series compensated ac system is considered in this study for design and analysis purpose. The design problem is formulated as an optimization problem and GSA is employed to search for the optimal controller parameters. The dynamic performance of the system under study is evaluated at various levels of series compensation with different types of disturbances. Fast Fourier Transform (FFT) analysis and robustness analysis against operating point changes and system uncertainties are also investigated. For specific system studied in the paper, the superiority of the GSA optimization technique over genetic algorithm (GA) optimization technique is also shown by comparing the simulation results and various performance indexes. Highlight: GSA optimized SSSC based sub-synchronous damping controller is proposed. IEEE second benchmark model with SSSC is considered for design and analysis. Fast Fourier Transform (FFT) analysis and robustness analysis are carried out. Nonlinear simulation results show better performance than GA approach.